Future Research of the Housing Supply System in Iran's Metropolises: A Case Study of Ahvaz Metropolis - Masoud Safaeepour; Fahime Fadaei Jazi (جغرافیا و برنامه‌ریزی محیطی, 2023)
AbstractThe aim of the current research was to identify the effective factors in the future state of housing planning in Ahvaz metropolis. The research method was applied based on the purpose and descriptive-analytical based on the nature. In this regard, by applying the mutual effects analysis method in Mikmak software, the key factors affecting the housing supply system of Ahvaz City were identified. Finally, the effective factors of the housing supply system in the mentioned city were selected by using the scenario writing method in the software and the scenario wizard was executed. The findings showed that the 7 factors of migration, marginalization, weakening of the value of national currency, low ability to pay loans, increase in land prices, insignificant credit facilities, and lack of an integrated and coordinated management system in the housing sector had the most impacts and key roles in the system. They provided housing in Ahvaz City.Keywords: future research, housing, housing supply, Ahvaz metropolis IntroductionIn recent decades, the cities of Iran have experienced an increasing concentration of population; yet, the weakness of economic management, lack of comprehensive housing planning, and inadequacy of the government's economic infrastructure have caused the problem of housing shortage and inadequate housing supply. The various policies and programs of the government have not led to good results either. The issue of the land market has caused a large part of lands in the capital to be attracted and ultimately, a large number of citizens to be deprived of shelter. Ahvaz metropolis in Khuzestan Province has undergone extensive demographic and spatial changes during the last decade for 3 main reasons: 1) having provincial centrality, 2) becoming a major industrial hub in line with adopting the policy of creating a growth hub, and 3) disrupting the order of the urban network as a result of the 8-year war and destruction of the major partner cities (Abadan and Khorramshahr) in favor of the all-round development of this city. As a result of these factors, the population of this city has had an increase of 120,098 to 1184,788 people during the years of 1956-2016). In the first general census of the country in 2015, Ahvaz had a population of 120,098 people. Therefore, this rapid population growth has caused problems, such as low quality of housing in the city, lack of ownership by a group of citizens, small areas of ​​residential units, etc. Based on this, this research sought to research the future of the housing supply system in Ahvaz metropolis to respond to the current and future needs and solve the existing problems in this city. In this regard, the main goal of the current research was to identify the most important factors influencing the future state of housing planning in Ahvaz metropolis. MethodologyThe main purpose of this research was to identify the most important factors influencing the future state of housing planning in Ahvaz metropolis. Therefore, a descriptive-analytical and survey method was chosen in this research. In the first step, a list of the primary factors that played a role in the housing supply system of Ahvaz City were identified as the research variables by using documentary sources and previous researches, as well as  the Delphi questionnaire. The research variables were analyzed based on an expert questionnaire. In the research process, by using the mutual effects analysis method and Micmac software, the influences of the primary factors on each other were evaluated in the form of the expert questionnaire. Finally, by using another questionnaire, the key factors of housing supply in Ahvaz City were selected via the scenario writing method in the Scenario Wizard software. The statistical population of the research included the specialists and experts of the urban area. The size of the studied sample was determined through the theoretical saturation of 30 experts through the snowball sampling method. The validity of the research tool was evaluated by university professors and it was confirmed after fixing the problems and deficiencies. To measure the reliability of the first expert’s questionnaire (analysis of mutual effects) and the second expert’s questionnaire (scenario writing), the questionnaire was completed by 10% of the experts and then, the results obtained from the supervisor could be cited and confirmed. DiscussionThe results showed that 7 key factors played a role in the housing supply system of Ahvaz City. As shown in Figure 3, these factors include migration, marginalization, weakening of the value of national currency, low ability to pay loans, increase in land prices, insignificant credit facilities, and lack of an integrated and coordinated management system in the housing sector. Also, the results revealed that the 3rd scenario was the most optimistic and promising scenario for the housing supply system of Ahvaz City with 5 favorable conditions and a suitable percentage of 42.87%. The 1st and 2nd scenarios were intermediate. The 2nd and 4th scenarios were respectively the most critical scenarios with unfavorable situations for the housing supply system of Ahvaz City. ConclusionHousing is one of the most essential human needs after food and clothing and it is very important for the preservation and survival of the individuals and society. It is related to one of the most basic and sensitive sectors in economic and social development planning. The rapid growth of population in Ahvaz City has caused problems, such as low quality of housing in the city, lack of ownership by a group of citizens, small areas of ​​residential units, inappropriate interference of activities by residing adjacent to the functional zones of the city, especially heavy industries and administrative-service zones, placement of extensive military, industrial, and wasteland uses in the middle of the residential context (one of the main factors of disintegration of the urban structure of this city), existence of the residential formal or informal settlements, like villages outside the legal boundaries and adjacent to the city, which have their own service and infrastructure needs, illegal constructions in the river boundary and encroachment on its bed, etc. In addition, financial and economic inabilities of low-income groups on the one hand and lack of modern planning and appropriate support mechanisms on the other hand have prevented the vulnerable groups from having access to suitable housing. This lack of access has shown itself in various forms of marginalization and ugly urban landscapes and has caused all kinds of social and economic problems. All these clearly reveal the necessity of fundamental change in the planning process from the traditional method based on forecasting trends towards modern planning with a forward-looking approach. Cities need to be planned with a new approach to recognizing the future challenges so as not to be caught off guard in the face of the upcoming challenges and can take control and manage a favorable future condition. References:- Alavi, A., Benari, S., & Samadi, M. (2017). Analysis of quantitative and qualitative indicators of housing in the city of Ahvaz and forecasting the required housing until 2021. Geography and Human Relations, Vol. 1, No. 2, pp. 867-850.- Arvin, M (2014). Survey of urban sprawl with an emphasis on endogenous development (Case study of Ahvaz City). Master's thesis in the field of geography and urban planning, University of Tehran, supervisor: Dr. Ahmad Pourahmad.- Iran Statistics Center (2015-2016).- Sherizadeh, A., Roostayi, Sh., & Hakimi, H. (2018). Identifying the key factors affecting the future status of low-income housing planning in Tabriz metropolis with a future research approach. Urban Research and Planning Quarterly, 10th year, No. 38, pp. 39-49.- Yazdani, M. H., Hasanpour, S., & Hashemi Masoumabad, R. (2018). Spatial analysis of social and physical dimensions of housing in the areas of Ahvaz City: Physical Development Planning. Scientific Research Journal, Year 4, No. 2, Serial 14, pp. 51-66.- Adeoye, D. O. (2016). Challenges of Urban Housing Quality: Insights and Experiences of Akure, Nigeria. Procedia-Social and Behavioral Sciences, 216, pp. 260-268.- Bharath, H. A. et al. (2018). Modeling urban dynamics in rapidly urbanizing Indian cities. The Egyptian Journal of Remote Sensing and Space Science, 21 (3), pp. 201-210. https: //doi.org/10.1016/j.ejrs.2017.08.002- Cobbinah, P. B. and Niminga-Beka, R. (2017). Urbanization in Ghana: Residential land use under siege in Kumasi central cities. 60, Part A, pp. 388-401. https: //doi.org/10.1016/j.cities.2016.10.011- Garbawaziri. A. and Roosli, R. (2013). Housing Policies and Programs in Nigeria: A Review of the Concept and Implementation. Business Management Dynamics.- Lamé, G., Jouini, O., & Cardinal, J. (2019). Methods and contexts: Challenges of planning with scenarios in a hospital’s division. Futures, Vol. 105, pp. 78-90.- Malpass, P. and Victory, C. (2010). The Modernization of Social Housing in England. International Journal of Housing Policy, 10 (1), pp. 3-18. DOI: 10.1080/14616710903565647- McClure, K. (2019). What should be the future of the Low-Income Housing Tax Credit program? Housing Policy Debate, 29 (1), pp. 65-81.‏- Miller, J. D. and Hutchins, M. (2017). The impacts of urbanization and climate change on urban flooding and urban water quality: A review of the evidence concerning the United Kingdom. Journal of Hydrology: Regional Studies, 12, pp. 345-362. https: //doi.org/10.1016/j.ejrh.2017.06.006- Moulaert, F. (Editor) et al. (2014). The International Handbook on Social Innovation: Collective Action, Social Learning, and Transdisciplinary Research. Cheltenham: UK Edward Elgar.- OCED (2015). How’s Life? Measuring Well-Being. DOI: http: //dx.doi.org/10.1787/how_life-2015-en- Pawson, H., Milligan, V., & Yates, J. (2020). Financing and Governing Affordable Rental Housing. In Housing Policy in Australia, Palgrave Macmillan, Singapore, pp. 259-298.‏- Pons, A. and Rullan, O. (2014). The expansion of urbanization in the Balearic Islands (1956-2006). Journal of Marine and Island Cultures, 3 (2), pp. 78-88. https: //doi.org/10.1016/j.imic.2014.11.004- Rowland, N. and Spaniol, M. (2017). Social foundation of scenario planning. Technological Forecasting and Social Change, Vol. 124, pp. 6-15.- Schwarts, A. F. (2014). Housing Policy in the United States.- Short, J. R. (2014). Urban theory: A critical assessment. Palgrave Macmillan.- UNDESA/PD (2012). World urbanization prospects: The 2011 revision. New York: United Nations.- Zedlewski, S. R. and Waller, M. (2002). The Importance of Housing Benefits to Welfare Success. Center on Urban & Metropolitan Policy and the Urban Institute.- Zhang, M. and Rasiah, R. (2016). Localization of state policy: Shandong's experience in financing Cheap Rental Housing in urban China. Habitat International, 56, pp. 1-10. https: //doi.org/10.1016/j.habitatint.2016.04.003 Figures and Tables- Table 1: Housing provision policies in Iran at different times- Table 1: Population of Ahvaz City during the years of 1956-2016- Fig. 1: Location of the study area (Vice President of Planning and Development of Human Capital of Ahvaz Municipality, 2022)- Table 3: Factors and components affecting the housing supply system of Ahvaz City- Table 4: Descriptive statistics of the respondents' status- Table 5: The direct and indirect effects of the factors on each other- Fig. 2: The distribution diagram of the variables in the impact-affectability axis based on the direct effects- Fig. 3: Factors affecting the housing supply system of Ahvaz City- Table 6: Key factors, situation, and possible assumptions facing the system- Table 7: Status of each of the key factors according to the compatible scenarios- Table 8: Coefficients, number, and percentage of each of the scenarios based on the 3 spectra